Fiscal-Monetary Mix and Exchange Rate Movements in the Major Industrial Countries, 1980-1984. (IMF Working Papers; Working Paper ;, 1988)
This paper analyzes the financial policies pursued in the major industrial countries under the flexible exchange rate regime, and links misalignments in policies and their mixes to exchange rate variations among the major currencies. A number of indicators note that misalignments in fiscal policy led to a corresponding divergence of fiscal and monetary policy mix among the industrial countries, and, together, contributed to the rapid appreciation of the dollar during the early 1980s. The continued liberalization of international capital movements and the differences in the savings rate also amplified the effects of policy divergences and their mixes on the exchange rate movements.